Malpractic in nursing: The experience in Turkey. Issue 6 (1st April 2014) - Karadağ, Gülendam; Ovayolu, Özlem; Parlar Kiliç, Serap; Ovayolu, Nimet; Göllüce, Aysun
Abstract : This cross‐sectional study was conducted with 562 nurses to find out nurses' opinions and practices concerning medical errors and to measure their tendency to make medical mistakes. Data were collected using a questionnaire and Tendency for Medical Errors Scale and evaluated using Student's t and one‐way ANOVA tests. The average total score of the participating nurses was 4.4 ± 0.3. It was observed that 36.1% nurses made medical errors, and all of those nurses making mistakes have stated that they have made medication errors. It was found that nurses with higher education and working in the intensive care unit had a lower tendency, whereas those working in children's hospital had a higher tendency to make medical mistakes ( P < 0.05). It might be recommended that the working conditions of nurses be improved, and nurses in general and particularly, those working with pediatric patients be given regular training to prevent drug administration errors.